1986 y-Walk participants signing in - Unknown:::Creator::::::::::::
Negative shows men and women who are participants in the 1986 y-Walk. They appear to be signing in at a set of tables and may be standing in different areas according to their last names. There are balloons at the tables and signs that indicate an alphabetical organizational method to signing in. The one readable sign says: "Callahan. Colbeck" and Joleen Callahan is standing next to it. Some of the women are wearing tee shirts that read: Walk for women. YWCA 1986." The tables are in a parking lot and there are trees and cars in the background.